The Effect of Applying the Problem-Based Learning Model on Students Critical Thinking Skills in the Topic of Ecosystem Components and Their Interactions in Grade X of SMAN 17 Medan in the Academic Year 2024/2025 - Frans Joko Purba; Tri Harsono (Florea : Jurnal Biologi dan Pembelajarannya, 2025)
Critical thinking skills are one of the essential 21st-century competencies that students must possess. However, in practice, during classroom learning at SMAN 17 Medan, students critical thinking skills are still relatively low due to the teacher-centered learning model being used. Therefore, a learning model that can encourage students to think critically is needed, one of which is the Problem-Based Learning (PBL) model.This study aims to determine the effect of the Problem-Based Learning model on students critical thinking skills. The research employed a quantitative method with an ex post facto research design, using a One Group Pretest-Posttest design. The sampling technique applied was purposive sampling. The research sample consisted of two classes, namely Class X-7 and Class X-8, both of which were treated with the same learning model, Problem-Based Learning, with a total of 70 students. The research instrument used to measure students critical thinking skills was an essay test. The results showed that the critical thinking skill scores in Class X-7 were 81.47 and in Class X-8 were 81.18. Data analysis using the paired sample t-test showed a significance value of 0.00 (Sig. < 0.05). Based on the results, it can be concluded that the implementation of the Problem-Based Learning model has a significant effect on the critical thinking skills of tenth-grade students in the subject of ecosystem components and their interactions at SMAN 17 Medan.